Lipoma Arborescens of the Upper Extremity With Anatomic Variation of the Palmaris Longus: A Case Report. Issue 3 (13th July 2022) - Kostas-Agnantis, Ioannis; Gkiatas, Ioannis; Korompilia, Maria; Kosmas, Dimitrios; Motsis, Efstathios; Pakos, Emilios; Korompilias, Anastasios
Abstract : Case: We present a case of a patient who suffered from wrist swelling and had symptoms of carpal tunnel syndrome. The patient underwent ultrasound and magnetic resonance imaging, in which signs of joint effusion and a fatty synovial lesion were presented. The treatment included open excision of the tumor. In addition, the palmaris longus muscle had an anatomic variation with proximal and distal tendon portions. The histopathological examination disclosed lipoma arborescens of the synovial membranes of the joints. Conclusion: The recognition of this entity and its characteristics are important not only for correct diagnosis but also for the appropriate treatment.